A prospective study of feline pleural effusion in University Veterinary Hospital - Zahri, Wirdatul Nazira (2014)
Pleural effusion is one of the common dyspnea condition in cats presented to University Veterinary Hospital (UVH). Number of pleural effusion cases presented has been recorded increased since 2008. Management in terms of diagnosis, treatment and client education for these cases has not been properly revised. Moreover, to date, no proper established data and nature of the condition been investigate. As a result, this study were conducted with the aim to study the prevalence of feline pleural effusion cases in UVH; determine the distribution of age, breed, sex and lifestyle factors; identify the most common fluid types and causes of pleural effusion and also to identify common bacterial isolated from fluid sample. Additional test of bacterial culture were performed to every fluid samples to determine the need of this test to be part of the routine diagnosis for pleural effusion. The result reveals a prevalence rate of 1.3% (n= 40/2,991) from cat population and 33 % (n=40/123) from dyspnea population obtained for pleural effusion cases presented within 6 months period. Majority of the cats presented are those between the age of 3 months to 1 year old 50 % (20/40) and were sexually intact male 52.5% (21140). Domestic Shorthaired (DSH) breed were over-presented with 77.5% (31/40) rate and cats with outdoor lifestyle are presented the most with 67.5% (27/40). Exudative effusion was predominantly presented at 65 % (24/34), with FIP (n=J3/34) and pyothorax (n= 11/34) become the common caused. Only sample from suspected pyothorax cases shows bacterial growth with 50% (11/22) rate and none in the rest of the sample. Rhodococcus equi appeared to be the most bacterial isolated from the fluid samples, with 72.7% (8/11) rate. These study demonstrate that although feline pleural effusion is not a common disease presented to UVH, it is however the highest respiratory condition manifested by dyspnea. It shows that FIP and pyothorax are the common cause of pleural effusion which also proves that FIP is primarily a disease of a young cats. Although other risk factor of breed, sex and lifestyle may contribute to the pleural effusion occurrence; it is very dependant on the underlying caused of the disease. The study also proves that bacterial culture is not a routine test to be performed as part of diagnosis of pleural effusion unless if pyothorax is suspected. The findings that Rhodococcus equi are the most common caused of pyothorax in cats would justify the needs of further investigation to be carry out to fully understand this new emerging disease.